2017
DOI: 10.1101/208678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decomposing parietal memory reactivation to predict consequences of remembering

Abstract: Memory retrieval can strengthen, but also distort memories. Parietal cortex is a candidate region involved in retrieval-induced memory changes as it reflects retrieval success and represents retrieved content. Here, we conducted an fMRI experiment to test whether different forms of parietal reactivation predict distinct consequences of retrieval. Subjects studied associations between words and pictures of faces, scenes, or objects, and then repeatedly retrieved half of the pictures, reporting the vividness of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 49 publications
8
17
0
Order By: Relevance
“…As such, it is possible that activation of event representations-supported by the parietal subnetwork (38)-should facilitate semantic or conceptual associations between contextually linked items, but at the cost of sensory detail. This prediction aligns with recent neuroimaging findings from Lee et al (39).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As such, it is possible that activation of event representations-supported by the parietal subnetwork (38)-should facilitate semantic or conceptual associations between contextually linked items, but at the cost of sensory detail. This prediction aligns with recent neuroimaging findings from Lee et al (39).…”
Section: Discussionsupporting
confidence: 92%
“…For example, van der Linder et al (19) found that increased angular gyrus activity accompanied memory benefits during schematic encoding. Recent work also indicates that retrieval-related activity in the parietal subnetwork is associated with increased generalization of episodic memories (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with these areas' role in the retrieval of semantic and schema-relevant information (Binder et al, 2009;Binder and Desai, 2011;Linden et al, 2017;Sommer, 2016), with some authors specifically highlighting these regions as hubs responsible for recombining or integrating schema-consistent information (Gilboa & Marlatte, 2017;Himmer et al, 2019;. Categorical reactivation in the same set of areas has previously been observed in a study investigating repeated memory retrieval (Lee et al, 2017), and the location of our semanticisation effects is thus largely consistent with the existing literature.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of location, both of our searchlights produced effects in the parietal cortex, generally highlighting the role of posterior association cortices in representing reactivated mnemonic content during recall (Lee et al, 2017) and imagery , and reflecting the dynamic change of these mental representations over time (Sommer, 2016). Interestingly, we found distinct sub-regions within the parietal lobe to track the changes on the categorical-semantic and the episodic-contextual level, with very little overlap between the two searchlight analyses (see Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 79%
“…Alternatively, posterior areas could start to represent items in a less detailed, more abstracted fashion. Some evidence for this latter suggestion comes from a recent study by Lee, Samide, Richter, and Kuhl 39 . The authors demonstrated that both specific item-level information as well as category level information could be decoded from AnG.…”
Section: Discussionmentioning
confidence: 95%